Less Steep Slope Stored More Soil C than Those Steep Ones: A Case Study in HPFU Samarinda - hartati, Wahjuni; Piri, Wandri L; Sudarmadji, Triyono; Syahrinudin, Syahrinudin (JURNAL AGRIMENT, 2024)
Global warming is a phenomenon of increasing global temperature of the earth from year to year due to the greenhouse effect that contains greenhouse gases (GHG) one of which is carbon dioxide (CO2), thereby increasing the absorption of heat released by the earth into the atmosphere, forests have a contribution as a provider of environmental services as an absorber of carbon dioxide (CO2). Hutan Pendidikan Fahutan Unmul (HPFU) is an area with forest status in Samarinda and is currently still dominated by land cover in the form of young secondary forest. this study was conducted to estimate the C reserves stored in the soil under the young secondary forest cover, determine its contribution to the total C reserves in the young secondary forest and estimate the potential of the total C reserves in the soil in HPFU. PUP is made measuring 20 m x 20 m on secondary forest cover with gentle slope (L2) to slightly steep (L3) at the top, middle, and bottom of the slope. In each slope do repetition as much as 3 times. In each PUP, a whole soil sample was taken using a sample ring and the soil was disturbed using a hoe at 3 depths,namely : 0-10 cm, 10-20 cm, and 20-30 cm. young secondary forest cover dominates the HPFU area on a gentle to rather steep slope. the C content of soil as deep as 30 cm in the sloping Slope area is 75.29 tons/ha with a total reserve of C is 5,499.80 tons and in a rather steep slope area is 54.69 tons/ha with a total reserve of C is 3,822. 83 tons